The Effect of the Treatment of Severe Early Childhood Caries on Growth-Development and Quality of Life - Ecenur Eyisoy Bagis; Sera Simsek Derelioglu; Fatih Sengül; Sinan Yılmaz (MDPI AG, 2023)
Purpose: Untreated early childhood caries (ECC) adversely affect children's quality of life. Our aim was to evaluate the effects of ECC on growth, development, and quality of life. Design and Methods: A total of 95 children were divided into three groups: general anesthesia (GA) (n = 31), dental clinic (DC) (n = 31), and control (n = 33). ECOHIS was applied to the parents in the GA and DC groups during a pre-treatment period and also applied in the post-treatment in the first and sixth months. Height, weight, and BMI measurements of the children in the study groups were taken and recorded at the pre-treatment stage and in the post-treatment in the first and sixth months. However, for the control group, these measurements were made just at the baseline and in the sixth month. Results: Upon the treatment of ECC, the total ECOHIS score significantly decreased (p < 0.001) in both groups in the following first month, whereas the scores of the children in the GA group reached a similar level to the DC group at the end of the sixth month. Following treatment, the weight and height of the children with ECC who initially had significantly lower BMI percentiles than the control group (p = 0.008) were observed to increase and, thus, they reached a similar BMI percentile value to the control group in the sixth month. Conclusions: The results of our study revealed that development and growth deficiencies in the children with ECC could be reversed rapidly by dental treatments and, thus, their quality of life would increase. The importance of treating ECC was revealed since treating ECC had positive effects both on the children's growth and development and on the quality of life of the children and their parents.